Effects of low molecular weight peptides from monkfish (Lophius litulon) roe on immune response in immunosuppressed mice - Ren, Zhexin; Yang, Fei; Yao, Sijia; Bi, Lijun; Jiang, Guanqin; Huang, Ju; Tang, Yunping (Frontiers in Nutrition, 2022)
This study aimed to investigate the immunomodulatory activation of low-molecular-weight peptides from monkfish (Lophius litulon) roe (named MRP) on cyclophosphamide (CTX)-induced immunosuppressed mice. Our results indicated that MRP (100 mg/kg/d BW) could significantly increase the body weight and immune organ index, and improve the morphological changes in the spleen and thymus of mice. These effects subsequently enhance the serum levels of interleukin (IL)-6, IL-1β, tumor necrosis factor (TNF)-α, and immunoglobulin (Ig) A, IgM, and IgG. Furthermore, MRP could also improve CTX-induced oxidative stress, and activate the NF-κB and MAPK pathways in the spleen tissues. The findings reported herein indicate that MRP has a good immunomodulatory activation toward immunosuppressed mice, hence can potentially be developed as an immune adjuvant or functional food.